Peningkatan Moralitas Peserta Didik Berkaitan dengan Profesinalitas dan Kompetensi Kepribadian Guru - Fachrurazi Fachrurazi (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2017)
Teacher is a professional educator on duty to develop students personality or known as student characters. In community, teacher personality considered as sensitive circumstances than pedagogical competency or professional. When a teacher does damaged action or norms violation in community, generally people inclined to react. This situation certainly as the results against school institution, where he works. Scientific evidences proved that teacher personality competency influenced to learning improvement and students personality. Some results of quantitative study confirmed that teacher personality competency has related and significance to motivate students achievements. Meanwhile result of qualitative study confirmed that teacher personality competency has contributed to students morality condition. Other results study confirmed that teacher personality appears influenced student interests and enthusiasm in learning process.